EFEKTIVITAS AROMATERAPI BITTER ORANGE TERHADAP NYERI POST PARTUM SECTIO CAESAREA - Utami, Sri (Unnes Journal of Public Health, 2016)
Surgery that causes severe pain physiological response as compared to a normal delivery was called sectio caesarea. The alternative to reduce pain with bitter orange aroma therapy. Bitter orange aroma therapy is to give the effect of reducing the muscle tensions and stress the body as a whole with the goal of keeping the body and mind into a relaxed. This research was aimed to explore the effectiveness of bitter orange aroma therapy for reduction pain in post partum sectio caesarea. The method used this research was quasi experimental with pre test and post test design with control group. The instruments used numeric rating scale to measure pain intensity. The sampling technique used purposive sampling where the quantity of research sample 34 respondents which are divided into 2 groups, namely intervention group and control group. bitter orange aroma therapy carried out for 15 minutes each day for 2 days. The univariate analysis was conducted to show pain distribution and bivariate analysis was conducted by Wicoxon and Mann Whitney. The result show that after bitter orange aroma therapy was applied towards intervered group, it was obtained that mean of respondents category pain was reducing at 3,44 (low pain) with the reduction was 1,47 and mean of post partum sectio caesarea pain without given bitter orange aroma therapy in control group was 4,82 (moderate pain) with the reduction was 0. The statistic showed up p value (0,000)< 0,05 which mean that kneading techniques effective to reduce pain of post partum sectio caesarea. Based on the result, bitter orange aroma therapy can be recommended as nursing intervention of post partum sectio caesarea.